A Review Article on the Therapeutic Potential of Medicinal Plants for Prevention and Treatment of Secondary Infection in Patients with COVID-19 - Rathore, Swati; Tiwari, Richa T.; Rai, Neha; Mahapatra, Debarshi Kar; Patil, Shailendra; Patil, Asmita Gajbhiye (Current Traditional Medicine, 2022)
COVID-19 is an infectious disease caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) that has rapidly spread all over the world, causing an international health crisis. Earlier, various synthetic antiviral drugs and clinical therapies have been used to control viral infections, but at present, there is no specific treatment available for COVID-19 infection. Several drugs, like ritonavir, lopinavir, hydroxychloroquine, and chloroquine, have been proposed. India is a hub of medicinal plants, so there is a chance to find effective means to combat the COVID-19 pandemic. The medicinal herbal formulations may enhance immunity and help develop a powerful antiviral drug, which is urgently needed to control the outbreak of coronavirus. In this review article, we have discussed the epidemiology, clinical outcomes, treatment, and prevention of this novel epidemic coronavirus from the medicinal herbal formulation perspective. We have also emphasized the reported antiviral activity and immunity-boosting properties of the Indian medicinal plants. This article also suggests that the drug or formulation obtained from plant sources would have low fatal outcomes, exhibit quick response, and be safe in the management and prevention of this pandemic outbreak.
Keywords: infectious disease